An analytical exposition of the European policies on maritime economy from their inception to present day. (1st January 2012) - Paixão Casaca, Ana Cristina
Since the establishment of the European Union, both European transport and maritime policies suffered from numerous ups and downs. Both of them came to be addressed on a continuous basis by the Council of the European Union, when the European Commission presented the 1985 Communication on the completion of the internal market where acknowledged that transport played an important role in the European economy. Since then and until today, numerous communications have been released to the extent that the transport infrastructure policy was split from transport policy, and today maritime transport falls within the scope of a broad integrated maritime policy . The present research work aims at investigating European transport and maritime policies from their inception to the very present day and at analysing their impact on the European maritime economy. The outcome of the paper shows that both transport and maritime policies increased their complexity due to the numerous background areas that they address today such as energy, environment and labour issues. Also, the present maritime policy contributes to devise a new maritime economy structure that can help the Europe Union to sustain its maritime role in the world economy.